Morphological and Functional Profile by Position in Female Football Players from Bogotá, SUB-15 Category (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2022)
The objective of this study was to determine the morphological and functional profile by position in female football players from Bogotá. The sample consisted of 81 players with an average age of 15.58 ± 0.85 years, height of 159.4 ± 5.36 cm, and body mass of 54.55 ± 6.82 kg, distributed across six positions: goalkeeper (GK, n = 8), central defender (CD, n = 13), lateral defender (LD, n = 14), central midfielder (CM, n = 18), lateral midfielder (LM, n = 11), and forward (FW, n = 17).The study employed a quantitative approach, non-experimental design, and descriptive type with non-probabilistic sampling. Field tests used included the Yo-Yo Intermittent Recovery Test Level 1, the Bangsbo sprint test, and 15- and 30-meter sprint tests, while strength was evaluated using uniaxial force platforms. Somatotype determination was performed using the Heath and Carter method. Statistical analysis was conducted using R version 4.1.0.Results showed significant differences between positions in variables such as body weight (p = 0.03), fat-free mass (p = 0.01), net force of the right leg at 100 ms [N] (p = 0.04), 150 ms [N] (p = 0.03), 200 ms [N] (p = 0.03), average repeated sprint ability (RSA) (p = 0.00), and fatigue percentage (p = 0.00).In conclusion, significant differences are linked to the role and position each player occupies during competition. Establishing the neuromuscular profile of athletes is therefore a key starting point for strengthening and structuring training processes in female football.